Shared Arctic Variable Framework Links Local to Global Observing System Priorities and Requirements - Bradley, Alice; Eicken, Hajo; Lee, Olivia; Gebruk, Anna; Pirazzini, Roberta (The Arctic Institute of North America, 2023)
The geographic settings and interests of diverse groups of rights- and stakeholders figure prominently in the need for internationally coordinated Arctic observing systems. Global and regional observing systems exist to coordinate observations across sectors and national boundaries, leveraging limited resources into widely available observational data and information products. Observing system design and coordination approaches developed for more focused networks at mid- and low latitudes are not necessarily directly applicable in more complex Arctic settings. Requirements for the latter are more demanding because of a greater need for cross-disciplinary and cross-sectoral prioritization and refinement from the local to the pan-Arctic scale, in order to maximize the use of resources in challenging environmental settings. Consideration of Arctic Indigenous Peoples’s observing priorities and needs has emerged as a core tenet of governance and coordination frameworks. We evaluate several different types of observing systems relative to the needs of the Arctic observing community and information users to identify the strengths and weaknesses of each framework. A typology of three approaches emerges from this assessment: “essential variable,” “station model,” and “central question.” We define and assess, against the requirements of Arctic settings, the concept of shared Arctic variables (SAVs) emerging from the Arctic Observing Summit 2020 and prior work by the Sustaining Arctic Observing Networks Road Mapping Task Force. SAVs represent measurable phenomena or processes that are important enough to multiple communities and sectors to make the effort to coordinate observation efforts worthwhile. SAVs align with essential variables as defined, for example, by global observing frameworks, in that they guide coordinated observations across processes that are of interest to multiple sectors. SAVs are responsive to the information needs of Arctic Indigenous Peoples and draw on their capacity to codesign and comanage ...